PENGARUH MODAL INTELEKTUAL TERHADAP KINERJA KEUANGAN PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI - Untara, Andini Permata (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out the influence of intellectual capital which is proxy with the Pulic Model (VAICTM) and the company performance that is proxy with the return on asset (ROA) on the company which has intensive intellectual capital asset which is banking companies.The population is banking companies which are listed in Indonesia Stock Exchange (IDX). The sample collection technique has bean determined by using purposive sampling and it is based on determined criteria therefore the samples are 27 banking companies which are consecutively never late to publish their financial statement during the period of 2008-2010. Multiple linier regressions with the SPSS application 2.0 versions are used in this research.The result of the research show that: 1)Value added capital employed (VACA), value added human capital (VAHU), and structural capital value added (STVA) have been fix in predicting the return on asset (ROA). 2) Value added capital employed (VACA) variable has significant influence to the return on asset (ROA). Moreover, the coefficient sign is positive showing the relationship between VACA and ROA is unidirectional. 3) Value added human capital (VAHU) variable has significant influence to the return on asset (ROA). But the coefficient regression shows a negative sign in which the relationship between VAHU and ROA is not unidirectional. 4) Structural capital value added (STVA) variable has significant influence to the return on asset (ROA). And the coefficient sign is positive showing the relationship between STVA and ROA is unidirectional.Keywords:Intellectual Capital, Return on Asset, Value Added Capital Employed, Value Added Human Capital, Structural Capital Value Added